The ology : ancient truths ever new - Machowski, Martin, 1963- (Greensboro, NC : New Growth Press, 2015)
"The Ology is a beautifully illustrated storybook that clearly explains transformative truths from the Bible. Within a traditional systematic theological framework, each truth is connected to the larger redemptive story of Scripture. The doctrine of God, for example, is presented in the larger framework of creation, where the attributes of God are on display and easier to understand. The addition of Bible references that support the truths in each spread and questions for further discussion make this a resource that families can use with all of their children. Families who read this book will be giving their children a gift that will last a lifetime--a solid foundation of biblical truth that will point them to the God who loves them and gave himself for them"-- Publisher description.
The ology of God. God always was and always will be ; God is three in one ; God created everything out of nothing at all ; God is all-powerful ; God is in control ; God knows all things ; God is everywhere ; God is perfect -- The ology of people. God created man and woman in his image ; The first husband and wife ; God walked with Adam and Eve in the garden -- The ology of sin. Sin ; Satan's first temptation ; Sin entered the world through Adam ; Sin separates us from God and from each other ; Sin always brings judgement ; God's promise of salvation ; God sent Adam and Eve out of the garden ; Sin spreads like a disease -- The ology of the promise and the law. God makes a promise ; God keeps his promise ; The ten commandments of God ; Breaking one law breaks the whole law ; God's holiness cannot be in the same place as sin ; God gave a way to cover sin ; Jesus is the sacrifice we need -- The ology of Christ. The son of God comes to earth ; The son stepped off his throne ; Jesus always loved god and people ; Jesus is completely human ; Jesus is completely God ; Jesus died in our place ; Jesus's resurrection defeated death ; We are safely hidden in Christ ; Jesus sends his disciples on a mission -- The ology of the Holy Spirit. Jesus promised to send the Holy Spirit ; The Spirit arrives on Pentecost ; The Holy Spirit : God's best gift -- The ology of adoption into God's family. Chosen ; Called ; Born again ; Faith ; Jesus paid it all ; Adopted -- The ology of change. Sin isn't in charge anymore ; Set apart, holy for God ; We grow a little at a time ; Put off the old, put on the new ; The Holy Spirit helps us fight against sin ; The fruit of the Spirit ; Running the race to the end -- The ology of the church. The church is built with living stones ; The church is God's temple ; We gather to worship ; The Lord's supper ; Baptism ; The gifts of the Spirit ; Persecution of the saints -- The ology of the end times. A picture of the future ; The return of Christ ; The final judgment ; A very different day for all God's children ; The new heavens and earth ; The special place where God lives with his people ; The final wedding -- The ology of God's word. God wrote the Bible through people ; God's word is true ; God talks to you and you talk to God ; The Bible is our spiritual food ; The Holy Spirit helps us understand God's word ; The word of God lives forever.
Keywords: Theology, Doctrinal; Christian education of children